Synthesis of cellulose acetate (CA) from algae Gracilaria sp. composited with nickel oxide (NiO) as a supercapacitor base material - Risdianto, I Wayan; Ahmad, Ahyar; Ermawar, Riksfardini Annisa (Communications in Science and Technology, 2023)
In this research, electrodes were made from cellulose acetate (CA) synthesized from algae Gracilaria sp. and then composited with nickel oxide (NiO), the concentration of which varied from 0, 0.2, 0.4, and 0.6 grams. Furthermore, FT-IR characterized cellulose acetate, and the CA-NiOn electrode was characterized by XRD, SEM, and cyclic voltammetry (CV). The results showed that CA was successfully synthesized from Gracilaria sp. Increasing the concentration of NiO added to CA as an electrode could increase the specific capacity, energy density, and power density of the electrode with the highest degree of 83.27 F/g, energy density of 4 Wh/kg, and a power density of 0.4 W/kg at a concentration of 0.6 gram NiO. The effect of the addition of NiO on the characteristics of the CA-NiOn electrode was also studied such as crystallinity, crystal size, and porosity. The presentation of CA doped with NiO has the promising prospects as a supercapacitor base material.